1994
DOI: 10.5014/ajot.48.7.633
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Occupational Therapy Education on Students’ Perceived Attitudes Toward Persons With Disabilities

Abstract: On the basis of these observations, a positive but nonlinear relationship between occupational therapy education and attitudes toward persons with disabilities was postulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 5 publications
1
31
0
1
Order By: Relevance
“…Three forms of the questionnaire are available: form O is the original form with 20 items; forms A and B, with 30 items, are improved versions of Form O. The tool has been consistently found to be reliable [5,25,33,34], and possess content and construct validity[25]. …”
Section: Resultsmentioning
confidence: 99%
“…Three forms of the questionnaire are available: form O is the original form with 20 items; forms A and B, with 30 items, are improved versions of Form O. The tool has been consistently found to be reliable [5,25,33,34], and possess content and construct validity[25]. …”
Section: Resultsmentioning
confidence: 99%
“…occupational therapy students) towards inclusion will determine why and how occupational therapy services are implemented within inclusive environments. As suggested in previous literature (Benham, 1988;Estes, Deyer, Hansen & Russell, 1991;Eagly & Chaiken, 1993;Lee, Paterson & Chan, 1994), the attitudes of occupational therapists and occupational therapy students towards inclusion may also play a significant role in the therapeutic relationship with students with disabilities.…”
Section: Introductionmentioning
confidence: 89%
“…The changes in ratings reflected in the then-test procedure were more strongly associated with changes in observed behavioural indicators of interviewing skill (median r = .33) and in judges' ratings of interviewing skills (median r = .43), than were changes reflected in the pretest/post-test procedure (median r values of ¡.05 and ¡.06, respectively). Studies using this methodology have examined the effectiveness of interventions in a variety of contexts, including teacher perceptions of effectiveness (Bray & Howard, 1980), level of job satisfaction (Gutek & Winter, 1992), perceptions of quality of life in cancer patients (Breetvelt & van Dam, 1991), effectiveness of a counsellor education programme (Manthei, 1997), and changing attitudes towards persons with disabilities (Lee, Paterson, & Chan, 1994). As just reported for Howard and Dailey (1979), a number of comparative studies have shown that results from retrospective analyses of change are more similar to objective ratings of change in behaviour or performance than are analyses using the pre/post procedure (Hoogstraten, 1982;Pohl, 1982;Sprangers & Hoogstraten, 1989).…”
mentioning
confidence: 99%